MDA, MDMA, and other "mescaline‐like" substances in the US military's search for a truth drug (1940s to 1960s). Issue 1 (5th December 2017) - Passie, Torsten; Benzenhöfer, Udo
Abstract: This article describes the context in which 3, 4‐methylenedioxyamphetamine (MDA), 3, 4‐methylenedioxymethamphetamine (MDMA) and other mescaline‐like compounds were explored as hallucinogens for military and intelligence purposes from the 1940s to the 1960s. Germans first tested mescaline as a "truth drug" in a military context. In the 1940s, the United States military started testing hallucinogenic substances as truth drugs for interrogation and behavior manipulation. After tests carried out using mescaline and other drugs in 1950, some derivatives of mescaline were synthesized by the Army for the exploration of possible "speech‐inducing" effects. After insufficient animal testing, the substances were given to patients at the New York State Psychiatric Institute (NYSPI). 3, 4‐Methylenedioxy‐ N ‐ethylamphetamine (MDE), a compound almost identical to MDMA, was among the compounds delivered for testing at the NYSPI. During tests with other derivatives (3, 4‐dimethoxyphenethylamine (DMA), 3, 4‐methylenedioxyphenethylamine (MDPEA), MDA) in 1952–53, an unwitting patient died in these tests, which was kept secret from the public. Research was interrupted and toxicological animal testing procedures were initiated. The secret animal studies run in 1953/1954 revealed that some of the "mescaline derivatives" tested (e.g. MDA, MDE, DMA, 3, 4, 5‐trimethoxyamphetamine (TMA), MDMA) were considered for further testing in humans. In 1955, the military changed focus to lysergic acid diethylamide (LSD), but some interest in mescaline‐like compounds remained for their ability to change mood and habit without interfering with cognition and sensory perception. Based on the known documents, it remains unclear (but probable) whether any of the mescaline derivatives tested were being used operationally. Abstract : This article describes the context in which MDA, MDMA, and other mescaline‐like compounds were synthesized and explored for their possible "speech‐inducing" effects for military and intelligence purposes between the 1940s the 1960s. Because mescaline was found to produce too much mental irritation and hallucinations, compounds with more specific effects were synthesized. MDA, MDE and MDMA (a.k.a. Ecstasy) were among the substances tested further in human and animal experiments.